Enhancing the Potential of Machine Learning for Immersive Emotion Recognition in Virtual Environment - M, Abinaya; G, Vadivu (EAI Endorsed Transactions on Scalable Information Systems, 2024)
Emotion recognition is an immense challenge for immersive technology. In order to detect the emotions of the user, we use machine learning methods and techniques to use the potential of the Virtual Environment and to improve the user Experience. Emotion recognition plays an important role in developing realistic and emotionally immersive experiences in augmented reality (AR) and virtual reality (VR) settings by instantly adjusting interactions, content, and visuals based on the accurate detection and interpretation of users’ emotions. Immersive systems can enhance user experience through various machine learning algorithms and methods used for emotion recognition, which are examined in this article. Upon novel idea, challenges and potential applications of incorporating emotion recognition in immersive virtual environments with Machine Learning (ML) Techniques and the benefits of tailoring powerful immersive experiences with ML methods were highlighted, and also the study discusses potential advancements in identifying the user’s emotion recognition in the future by modeling an Architecture, as well as how the ML techniques were enhanced for virtual environment is discussed.